Purification and characterization of lipase from newly isolated Burkholderia multivorans PSU-AH130 and its application for biodiesel production - Chaiyaso,T. (Springer Heidelberg, 2015)
An extracellular lipase from newly isolated Burkholderia multivorans PSU-AH130 was purified 21.6-fold with a yield of 12.1% by (NH4) 2SO4 precipitation, ion exchange chromatography (DEAE-Toyopearl) and gel filtration chromatography (Sephadex G-150). The purified lipase from B. multivorans PSU-AH130 was homogeneous as determined by SDS-PAGE, with an apparent molecular mass of 58 kDa. The N-terminal sequence of the lipase was AAEDRDWMSS, which is different from most other reported lipases. The purified lipase showed optimal activity at pH 8.0 and 55°C. The enzyme was stable at pH range 7.0-9.0 and temperatures between 35°C and 60°C. Its halflife was 2 h at 65°C. The Km and Vmax of the enzyme were 1.6×10-3 M and 1,000 U/mg protein, respectively, using pnitrophenyl palmitate (pNPC16) as a substrate at pH 8.0. It was active toward p-nitrophenyl ester with medium-to-long acyl chains (C 8-C16), and showed maximum activity with pnitrophenyl caprylate (pNPC8). The lipase activity was inhibited by Zn 2+, Co2+, Mn2+, Cu2+, EDTA, ammonium persulfate and some organic solvents, e.g., acetone, dioxane and pyridine, whereas Ca2+ and K+ stimulated its activity. The immobilized lipase from B. multivorans PSU-AH130 on Accurel EP100 (IM-PSU-AH130) showed the highest fatty acid methyl ester (FAME) yield of 82.7% after a reaction time of 72 h, compared to yields obtained with other immobilized commercial lipases, i.e., IM-PS from Pseudomonas cepacia (78.5%), IM-AK from P. fluorescens (78.0%) and IM-D from Rhizopus delemar (27.7%), respectively. © 2012 Springer-Verlag and the University of Milan.